A Novel Hypothalamic Factor, Neurosecretory Protein GM, Causes Fat Deposition in Chicks - Kato, Masaki; Iwakoshi-Ukena, Eiko; Furumitsu, Megumi; Ukena, Kazuyoshi (Frontiers in Physiology, 2021)
We recently discovered a novel cDNA encoding the precursor of a small secretory protein, neurosecretory protein GM (NPGM), in the mediobasal hypothalamus of chickens. Although our previous study showed that subcutaneous infusion of NPGM for 6 days increased body mass in chicks, the chronic effect of intracerebroventricular (i.c.v.) infusion of NPGM remains unknown. In this study, we performed i.c.v. administration of NPGM in eight-day-old layer chicks using osmotic pumps for 13 days. In the results, chronic i.c.v. infusion of NPGM for 13 days significantly increased body mass, water intake, and the mass of abdominal and gizzard fat in chicks, whereas NPGM did not affect food intake, liver and muscle masses, or blood glucose concentration. Morphological analyses using Oil Red O and hematoxylin-eosin stainings revealed that fat accumulation occurred in both the liver and gizzard fat after NPGM infusion. The real-time PCR analysis showed that NPGM decreased the mRNA expression of peroxisome proliferator-activated receptor α, a lipolytic factor in the liver. These results indicate that NPGM may participate in fat storage in chicks.